In situ/operando XAFS investigation of the sorption/precipitation of Zn(II) on palygorskite surface at the molecular scale: Implications for Zn stable isotope fractionation. (15th May 2023) - Mo, Xinxin; Takahashi, Yoshio; Siebecker, Matthew G.; Gou, Wenxian; Wang, Zhao; Lu, Xiancai; Li, Wei
Abstract: In aqueous geological environments, the fate and transport of Zn are controlled by geochemical reactions (e.g., sorption) occurring at the mineral/water interface. However, many of the underlying Zn fixation mechanisms, especially the kinetics of surface-induced precipitation, are still unclear. Additionally, Zn stable isotope fractionation during sorption has recently been shown to be an important process, but the relationship between Zn isotope fractionation and sorption mechanisms (e.g., surface complexation, precipitation) is also not well understood. To address these issues, we employed X-ray absorption fine structure (XAFS) spectroscopy, high-resolution transmission electron microscopy (HRTEM), and in situ/operando quick-scanning XAS (QXAS) spectroscopy to elucidate the sorption/precipitation mechanisms of Zn at palygorskite/solution interfaces. We also measured Zn isotope ratios during some sorption experiments to illustrate how Zn isotope fractionation behavior is affected by the evolution of coordination environments at different pH values, initial concentrations, and reaction times. Our results demonstrate that Zn sorption mechanisms vary as a function of pH, ionic strength, initial concentration, and reaction time. At low pH (pH < 7.0) and low ionic strength (I ≤ 0.01 M), Zn(II) predominantly forms an outer-sphere surface complex in octahedral coordination. At low pH (pH < 7.0) and high ionic strength (I = 0.1 M), Zn(II) is predominantly sorbed as an inner-sphere octahedral surface complex with insignificant isotopic fractionation (Δ 66 Znsorbed-aqueous = −0.02 ± 0.05‰). At high pH and high initial Zn concentration (pH 7.5, C0 ≥ 0.2 mM), the formation of octahedral Zn phyllosilicate precipitates is observed, yielding a small fractionation with an average Δ 66 Znsorbed-aqueous of 0.10 ± 0.07‰. In addition, in situ/operando QXAS of Zn sorption at pH 7.5 in a flow cell revealed that the predominant sorbed Zn species shifted from inner-sphere tetrahedral complexes during the initial stage (e.g., within minutes) to inner-sphere octahedral complexes during later stages (e.g., within hours), followed by the formation of Zn-phyllosilicate precipitates (e.g., within days). This molecular evidence coincides with the evolution of Zn isotope fractionation from a large Δ 66 Znsorbed-aqueous value (0.53 ± 0.05‰) to a small value of 0.05 ± 0.04‰ during the sorption process. The combination of QXAS and isotope fractionation results reveals a change in the Zn local environment from tetrahedral coordination to octahedral coordination. The findings in this study not only provide new insight into surface adsorption/precipitation mechanisms but also demonstrate that stable isotope fractionation is linked with the local molecular/bonding environments at mineral–water interfaces.